Diseases Caused by Xylella fastidiosa in Prunus Genus: An Overview of the Research on an Increasingly Widespread Pathogen - Greco, Davide; Aprile, Alessio; De Bellis, Luigi; Luvisi, Andrea (Frontiers in Plant Science, 2021)
Cultivated plants belonging to the genus Prunus are globally widespread, and for some countries are economically important crops as well as playing a key role in the composition of the landscape. Xylella fastidiosa is a key threat to plant health, and several Prunus species are heavily stressed by this pathogen - such as almond, peach and plum - and many strain types of different subspecies can cause severe diseases. This review highlights the different approaches to managing the epidemic events related to X. fastidiosa in stone fruit. In fact, in most European and Asian new outbreaks, almond is a very common host or even the main one, and peach, plum, apricot and cherry are widespread and profitable crops for the involved areas. The various diseases associated with stone fruit plants show different degrees of severity in relation to the cultivar, although investigations are still limited. The development and selection of tolerant and resistant cultivars and the study of the resistance mechanisms activated by the plant against X. fastidiosa infections seems to be the best way to find long term solutions aimed at recovering the affected areas. In addition, observations in orchards Xylella fastidiosa in stone fruits severely affected by the disease can be essential for collecting tolerant or resistant material within the local germplasm. In areas where the bacterium is not yet present, a qualitative quantitative study on the entomofauna is also important for the timely identification of potential vectors and for developing effective control strategies.